Dissolution of polycyclic aromatic hydrocarbons from weathered contaminated soil - Yeom, IT; Ghosh, MM; Cox, CD; Ahn, KH (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
Dissolution of PAHs from soil contaminated with multi-component coal tar was investigated using a polymeric adsorbent, Tenax-TA and a nonionic surfactant, Brij 30. Tenax created maximum concentration gradient at the soil/water interface, thus maximizing interfacial mass transfer. Even in the presence of Tenax, the release of PAHs from the weathered soil was a very slow, noneqilibrium process. The rate-limiting step in the release of PAH was identified as diffusional mass transfer within the contaminant-soil matrix. Based on model analyses, the key parameter controlling dissolution of PAHs from the soil was found to be the diffusivities of PAHs within the soil/tar matrix. Brij 30 solution (5.5 g/L) substantially increased the rate of PAH dissolution from the soil. The enhanced mass transfer rates of PAHs by Brij 30 were attributed to their enhanced matrix diffusivities rather than their increased aqueous solubilities. Matrix diffusivities of PAHs in Brij 30 solution increased by two orders of magnitude compared with those with Tenax. Swelling of the weathered tar matrix of the soil by infiltrating surfactant molecules was suggested as the mechanism responsible for the observed diffusivity enhancement. Copyright (C) 1996 IAWQ.
Keywords: HYDROPHOBIC ORGANIC-CHEMICALS; DESORPTION-KINETICS; SORPTION KINETICS; BIOREMEDIATION; PARTITION; SEDIMENT